Chiglitazar diminishes the warburg effect through PPARγ/mTOR/PKM2 and increases the sensitivity of imatinib in chronic myeloid leukemia - Hongpeng Duan; Qian Lai; Yuelong Jiang; Liuzhen Yang; Manman Deng; Zhijuan Lin; Weihang Shan; Mengya Zhong; Jingwei Yao; Li Zhang; Bing Xu; Jie Zha (Experimental Hematology & Oncology)
Abstract Background A tyrosine kinase inhibitor (TKI) such as Imatinib (IM) is the preferred treatment for Chronic Myeloid Leukemia (CML). However, the emergence of IM resistance presents a significant challenge to disease management. A characteristic of cancer cells, including IM-resistant CMLs, are characterized by heightened uptake of glucose and aberrant glycolysis in the cytosol, which is known as the Warburg effect. In addition to its potential to modulate the Warburg effect, Chiglitazar (Chi), a compound that regulates glucose metabolism, has also been investigated for its implication in cancer treatment. This suggests that combining Chi with IM may be a therapeutic strategy for overcoming IM resistance in CML. Methods Sensitive and IM-resistance CML cells were treated with Chi in vitro, followed by detecting of extracellular acidification rate (ECAR) using a Seahorse XF Analyzer. CML cell proliferation, cell cycle distribution, and apoptosis were tested by CCK-8 assay and flow cytometry. RNA sequencing was utilized to investigate potential transcriptional changes induced by Chi usage. In vivo studies were conducted on immunodeficient mice implanted with CML cells and given Chi and/or IM later. Tumor growth was monitored, as well as tumor burden and survival rates between groups. Results Our metabonomic, transcriptomic, and molecular biology studies demonstrated that Chi, in part, diminished the Warburg effect by reducing glucose and lactate production in imatinib-resistant CML cells through the PPARγ/mTOR/PKM2 pathway. This modulation of glucose metabolism resulted in reduced cell proliferation and enhanced sensitivity to IM in imatinib-resistant CML cells in vitro. Rescue assay by introducing shPPARγ or mTOR activator verified the underlying regulatory pathway. Also, the combination of Chi and IM synergistically increased the sensitivity of IM in vivo and prolonged the survival of imatinib-resistance CML transplanted mice. Conclusions Our results demonstrated the potential of Chi to overcome IM resistance in vitro and in vivo. By inhibiting the Warburg effect through the PPARγ/mTOR/PKM2 pathway, Chi resensitizes CML cells towards imatinib treatment. Combining IM with Chi is an alternative therapeutic option for CML management, especially for IM-resistant CML patients.